Controlled reproduction of wild Eurasian Perch : a hatchery manual - Żarski, Daniel; Horváth, Ákos; Bernáth, Gergely; Krejszeff, Sławomir; Radóczi, János; Palińska-Żarska, Katarzyna; Bokor, Zoltán; Kupren, Krzysztof; Urbányi, Béla (Springer, 2017)
The work summarizes the current knowledge regarding the controlled reproduction of an emerging aquaculture species, the Eurasian perch (Perca fluviatilis). In great detail it describes and explains the principal of most of the controlled reproductive protocol leading to obtain high quality larvae. The book is primarily intended to be used as a hatchery manual by practicing aquaculturists and laboratory technicians working with this species. On the other hand, it also summarizes the scientific background of the methods applied, therefore, it can serve as a reference for the state-of-the-art in the controlled reproduction of Eurasian perch and other freshwater percid species.
Keywords: Perch -- Reproduction.; Aquaculture.; elektronické knihy; electronic books